2010
DOI: 10.1080/11263500903374724
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal communities associated withTuber magnatum‐productive niches

Abstract: Truffles are hypogeous ectomycorrhizal fungi of ecological interest for forestry in soils of the northern hemisphere, and of economical relevance for food markets worldwide. The molecular mechanisms that control truffle body formation are largely unknown, as well as the environmental factors that are likely involved. Among the latter, it has been hypothesized that soil-borne communities may have an impact on truffle production. To address this question, we investigated bacterial and fungal communities resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Similarly, Tuber melanosporum ectomycorrhizae were found to harbour distinct bacterial communities from those of the bulk soil, with an enrichment in αand γ-Proteobacteria, as reflected by the amplicon pyrosequencing of PCR-barcoded libraries (Deveau et al, 2016). The investigation of communities that are resident in productive versus adjacent non-productive grounds of the white truffle, Tuber magnatum, by using PCR-denaturing gradient gel electrophoresis, found that a bacterium identified as Moraxella osloensis was associated with a productive site, and that the fungi Mortierella and Fusarium oxysporum also appeared to be more abundant in the productive area (Mello et al, 2010). Although the significance of enhanced levels of Moraxella for truffle production is unclear, Mortierella spp.…”
Section: Cultivated Ascomycetes On Soilmentioning
confidence: 99%
“…Similarly, Tuber melanosporum ectomycorrhizae were found to harbour distinct bacterial communities from those of the bulk soil, with an enrichment in αand γ-Proteobacteria, as reflected by the amplicon pyrosequencing of PCR-barcoded libraries (Deveau et al, 2016). The investigation of communities that are resident in productive versus adjacent non-productive grounds of the white truffle, Tuber magnatum, by using PCR-denaturing gradient gel electrophoresis, found that a bacterium identified as Moraxella osloensis was associated with a productive site, and that the fungi Mortierella and Fusarium oxysporum also appeared to be more abundant in the productive area (Mello et al, 2010). Although the significance of enhanced levels of Moraxella for truffle production is unclear, Mortierella spp.…”
Section: Cultivated Ascomycetes On Soilmentioning
confidence: 99%
“…Revolutionary insight into the truffle ecosystem dynamics based on a set of metagenomic techniques (Napoli et al, 2008Mello et al, 2010Mello et al, , 2011 suggests, but does not prove, that allelopathy may be operative in the brûlé. It should be mentioned that the allelopathic potential of truffles has already been taken into consideration by a number of researchers (Tirillini & Granetti, 1995;Tirillini & Stoppini, 1996;Chevalier, 1998;Olivier et al, 2002;Splivallo, 2007;Angelini et al, 2009).…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…These approaches allowed insights into mycorrhizal community of the productive spots of T. magnatum -showing that the mycorrhizae of this fungus are generally rare and most roots of the host trees are occupied by other mycorrhizal fungi (Murat et al 2005). Molecular analysis of bacterial and fungal communitites associated with the productive spots of T. magnatum failed to identify any specific fungi associated with this truffle, whereas they suggested a bacterium Moraxella osloensis (a gamma-Proteobacterium) to be preferentially associated with the productive spots of this truffle (Mello et al 2010). Our previous study (Gryndler et al 2012) revealed a specific association of some bacteria, including four genera of actinobacterial suborder Pseudonocardineae, with ectomycorrhizae of Tuber aestivum Vittad.…”
Section: Introductionmentioning
confidence: 98%